Magnetic Binary Silicide Nanostructures. Issue 41 (2nd May 2018) - Goldfarb, Ilan; Cesura, Federico; Dascalu, Matan
Abstract: In spite of numerous advantageous properties of silicides, magnetic properties are not among them. Here, the magnetic properties of epitaxial binary silicide nanostructures are discussed. The vast majority of binary transition‐metal silicides lack ferromagnetic order in their bulk‐size crystals. Silicides based on rare‐earth metals are usually weak ferromagnets or antiferromagnets, yet both groups tend to exhibit increased magnetic ordering in low‐dimensional nanostructures, in particular at low temperatures. The origin of this surprising phenomenon lies in undercoordinated atoms at the nanostructure extremities, such as 2D (surfaces/interfaces), 1D (edges), and 0D (corners) boundaries. Uncompensated superspins of edge atoms increase the nanostructure magnetic shape anisotropy to the extent where it prevails over its magnetocrystalline counterpart, thus providing a plausible route toward the design of a magnetic response from nanostructure arrays in Si‐based devices, such as bit‐patterned magnetic recording media and spin injectors. Abstract : While binary transition‐metal and lanthanide silicides are not magnetic materials in their bulk form, there are numerous reports on magnetic properties of these very silicides when they are grown as epitaxial nanostructures. Recent progress in the field of epitaxial magnetic silicides is surveyed, and plausible reasons behind the unexpected ferromagnetic order in these important technological materials is suggested.